PINE: An Energy Efficient Flexibly Interconnected Photonic Data Center Architecture for Extreme Scalability - Bergman, Keren; Shalf, John; Michelogiannakis, George; Rumley, Sebastien; Dennison, Larry; Ghobadi, Manya (Optical Interconnects (invited paper), 2018)
The cost and complexity of existing interconnects prevent designing datacenter racks tailored to emerging applications such as machine learning. We introduce the PINE interconnect (Photonically Interconnected datacenter Elements), in which compute, memory or storage modules are flexibly combined through one-model-fits-all embedded photonic connectivity and better utilize distant resources.